2020
DOI: 10.1155/2020/7837213
|View full text |Cite
|
Sign up to set email alerts
|

Skull Abnormalities in Cadavers in the Gross Anatomy Lab

Abstract: Background. The skull encompasses and houses one of the most important organs in the body-the brain-and like all tissues in the body, it is comprised of living cells that are constantly remodeling as this maintains the strength and homeostasis of the bone. In the present study, abnormal bone growth patterns were observed and the possible causes of said findings were investigated in multiple cadaver skulls dissected during head and neck anatomy courses at Detroit Mercy Dental over the past year. There are many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…High CI has been reported in patients with schizophrenia 7 . A cadaver study identified irregular undulating and thickening of the frontal bone internal surface in patients with Alzheimer’s disease, dementia, depression, and PD 6 . These findings suggest a potential association between cranial morphology and neuropsychiatric disorders, including PD.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…High CI has been reported in patients with schizophrenia 7 . A cadaver study identified irregular undulating and thickening of the frontal bone internal surface in patients with Alzheimer’s disease, dementia, depression, and PD 6 . These findings suggest a potential association between cranial morphology and neuropsychiatric disorders, including PD.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, few studies have focused on skull geometry in adults. In a cadaver study, 19 of 65 specimens (29%) showed irregular undulating and thickening of the frontal bone internal surface, of which 5 specimens (26%) were of patients diagnosed with neurological disorders, including Alzheimer's disease, dementia, depression, and PD 6 . Nagaishi et al used computed tomography (CT) to investigate skull morphological changes 7 and showed that cranial shape significantly differed between patients with moyamoya disease, cervical internal carotid artery stenosis, depression, or schizophrenia and control participants.…”
Section: Introductionmentioning
confidence: 99%
“…A região glabelar é a uma elevação suave da linha média, entre as duas sobrancelhas., numa posição quase central na face 3 . Os arcos superciliares são a parte óssea proeminente logo acima do terço medial das margens supraorbitais, 4 sendo mais proeminentes nos homens do que nas mulheres. A glabela está próxima aos seios frontais e ao nasio e fornece fixação às fibras da parte orbital do orbicular do olho e do músculo prócero.…”
Section: Introductionunclassified